Strain-based assessment of liquefaction and seismic settlement of saturated sand. Issue 1 (1st January 2019) - Hazirbaba, Kenan; Omarow, Maksat
Abstract: This study presents results from an extensive experimental research on saturated clean sand deposits subjected to seismic loading. A total of 29 freshly reconstituted soil samples were tested under laboratory conditions. Strain-controlled, undrained, cyclic triaxial tests were conducted to evaluate the excess pore water pressure and associated settlement response of soil to seismic loading. The level of induced cyclic shear strain varied between 0.01% and 0.5%. The generation of excess pore water pressure was measured under various consolidation stresses ranging from 100 kPa to 400 kPa. Additionally, the settlement due to the dissipation of the excess pore pressure was measured and analyzed for each level of consolidation stress. The findings from the experimental work were used for liquefaction and seismic assessment of an actual soil deposit. A scenario earthquake of magnitude Mw  = 7.2 with peak ground acceleration ( PGA ) of 0.42 g was considered. Induced shear strains at various depths of the soil deposit were determined using software ProShake. It was found that relatively shallower depths were less prone to liquefaction with insignificant cyclic settlement.